Project-based carbon contracts: A way to finance innovative low-carbon investments - Jörn C. Richstein (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Low and uncertain carbon prices are often stated as a major obstacle for industrial sector investments in technologies to deliver deep emissions reductions. Project-based carbon contracts underwritten by national governments could addressregulatory risk, lower financing costs and strengthen incentives for emission reductions at investment and operation stage. In this paper design options for project-based carbon contracts are assessed using an analytical model capturing risk aversion of investors with a meanvariance utility function. The model is also used to assess how a combination with grant support for innovative projects can minimize overall costs of innovation policy. Savings in financing costs are quantified using a stylized project finance cash flow analysis.
Keywords: D81; Q48; Q54; Q55; Q58; O38; 330; emission trading systems; carbon contract; innovation support